Lethal and Sublethal Effects of Pyrrolizidine Alkaloids of Senecio rudbeckiaefolious against Diatraea saccharalis F. Larvae - Terán, Paula Maria (2019)
Diatraea saccharalis Fabricius (Lepidoptera: Crambidae) is the most damaging sugarcane pest in the Northwestern Argentina and an important pest in corn in the Pampas region. Larvae perforate the stem of the cane forming galleries or tunnels in its interior, which decreases the flow of water and nutrients and facilitates the entry of pathogens. Infestations by this insect provoke significant economic losses. Given the environmental and human health impact of control measures based on the application of agrochemicals, the current study was based on the use of bioactive natural products, such as plant secondary metabolites. The objective of this work was to study the alkaloidal composition of a methanolic extract from Senecio rudbeckiaefolious Meyen and Walp (Asteraceae) and to evaluate its lethal and sublethal effects against the larvae of sugarcane borer, D. saccharalis. The major components detected in the pyrrolizidine alkaloids (PAs) fraction were senecionine and integerrimine. Repellency and toxicity bioassays were carried out with larvae fed on a diet supplemented with an aqueous solution of PAs (50-200 mg/L). No repellent effect was observed. Concentration-dependent mortality and a marked inhibitory action of larval growth were recorded. The results suggested that PAs could be promising biopesticidal compounds for D. saccharalis control.